Práticas de acolhimento e produção do cuidado em um Centro de Atenção Psicossocial álcool e outras drogas - Oliveira, Carolina Galvão de (2016)
In this study we intended to follow user embracement practices in the everyday life of an Alcohol and Drugs Psychosocial Attention Center (CAPS ad) located in the city of Campinas (SP), and analyze the care assistance produced in relations between workers and users of the service. To achieve these intentions in nine months of empirical research, we used observations, everyday conversations, interviews and one workshop with the CAPS workers. We used the French Institutional Analysis references and field diaries as a tool for the production of research data and to analyze the implications of the researcher, in a denaturalized perspective. To help our analysis, we searched for the polysemy notions of care and user embracement in the health field and its links to the drugs public politics. We also used ideas of the Collective Health field, which refer user embracement as a work methodology and a reorganization strategy for health services as well, operating soft technologies of relations. Through everyday conversations we were able to describe different practices of user embracement and distinguish situations that interrogates the workers potencial to create new responses to the problems faced, just as traditional psychiatric vestiges as well. We were able to identify that when user embracement practices are dedicated to the users most distinctive expressions, they show potential to increase the access to health care in a Risk and Harm Reduction perspective, stimulating deinstitutionalization processes at mental health, alcohol and drugs field